PENGARUH KOMBUCHA SARI BUAH BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Yuly Diyan Nur Fajriyah; Dwi Wahyuni; Siti Murdiyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2015)
Kombucha is a fermented drink from nata kombucha starter which is symbiosis between Acetobacter sp. And Saccharomyces sp. Which were grown in medium of A. bilimbi. A. bilimbi kombucha produces various types of acids, enzymes, alcohol and vitamins in addition A. bilimbi fruit contain flavonoids, alkaloids, triterpene saponins, terpenoids, and essential oil. This study aimed to analyze the influence of A. bilimbi kombucha on growth of E. coli. This kombucha has an antibacterial activity on E. coli growth. E. coli is a diarrhea causing bacterium. Concentration of kombucha used were 25%; 27.5%; 30%; 32.5%, and 35%. Antibacterial test using a pour plate method. Analysize tested using one way ANOVA and followed by post hoc test LSD with 95% levelof confidence. This research showed that Averrhoa blimbi kombucha perform antibacterial activity against E. coli and at concentration of 35% kombucha buluh perform inhibition which different significally (p>0.05). Keywords: A. bilimbi, A. bilimbi kombucha, E. coli.